6. In Vitro Insecticidal Activities of Ethanol Extract of Neem Leaves Against Heterodoxus Spiniger Lice In Dogs - I Made Merdana; Monica Lewinsky; Ida Ayu Pasti Apsari (Universitas Syiah Kuala, 2020)
Heterodoxus spiniger is a chewing lice that have been reported to infest dogs and cats. This ectoparasite is haematophagous and as an intermediate host in transmission of cysticercoids and egg of nematode worms. This study aims to determine the in vitro insecticidal activity of ethanol extract of neem leaf (Azadirachta indica) against H. spiniger. A total of 250 H. spiniger were divided into five groups with five replications, namely: P0 as a negative control group given placebo, P1 as a positive control group given deltamethrin 0.5EC 0.05%, and groups P2, P3 and P4 were given ethanol extract of neem leaves with concentrations of 2.5%, 5% and 10%. In each test, 10 lice samples were put into a petridish with a cotton swab that had been sprayed with the solution of each treatment, then the lice were treated again with fine spray evenly. The results showed that the in vitro ethanol extract of neem leaves had a very significant effect (P0.01) on the mortality of H. spiniger. The best results are shown at 5% concentration which is capable of killing 100% of lice in 30 minutes. It can be concluded that the ethanol extract of neem leaf has insecticidal activity against H. spiniger.